Analysis of CO2 Emission Generation in the Transportation and Mining Sector in Banawa District, Donggala Regency - Amini, Novira Putri; Cahyonugroho, Okik Hendriyanto (Jurnal EnviScience (Environment Science), 2023)
Donggala Regency is an area traversed by a national road connecting two provinces in Sulawesi and is also the largest supplier of class C minerals in Indonesia. Both sectors are contributors to CO2 emissions in the air. It is necessary to carry out an emissions inventory to provide an overview of air quality and an indication of air condition in the environment. The primary purpose of an emissions inventory is to analyze the sources of exhaust gases that emit pollutants into the atmosphere. This study aims to provide an inventory of CO2 emissions from the transportation and mining sectors in Banawa District, Donggala Regency using the IPCC. The results showed that the CO2 emissions generated from the transportation and mining sectors at the research location amounted to 5,401.11 tonsâˆ™year-1. The types of vehicles that produce the most CO2 are minibuses and motorcycles. The generation of CO2 emissions in the mining sector is not that large because the location and heavy equipment used do not have large quantities.